Effect of varying dietary levels of LC-PUFA and vegetable oil sources on performance and fatty acids of Senegalese sole post larvae: Puzzling results suggest complete biosynthesis pathway from C18 PUFA to DHA - Navarro-Guillén, Carmen (2014)
Lipid nutrition of marine fish larvae has focused on supplying essential fatty acids (EFA) at high levels to meet requirements for survival, growth and development. However, some deleterious effects have been reported suggesting that excessive supply of EFA might result in insufficient supply of energy substrates, particularly in species with lower EFA requirements such as Senegalese sole (Solea senegalensis). This study addressed how the balance between EFA and non-EFA (better energy sources) affects larval performance, body composition and metabolism and retention of DHA, by formulating enrichment emulsions containing two different vegetable oil sources (olive oil or soybean oil) and three DHA levels. DHA positively affected growth and survival, independent of oil source, confirming that for sole post-larvae it is advantageous to base enrichments on vegetable oils supplying higher levels of energy, and supplement these with a DHA-rich oil. In addition, body DHA levels were generally comparable considering the large differences in their dietary supply, suggesting that the previously reported ∆4 fatty acyl desaturase (fad) operates in vivo and that DHA was synthesized at physiologically significant rates through a mechanism involving transcriptional up-regulation of ∆4fad, which was significantly up-regulated in the low DHA treatments. Furthermore, data suggested that DHA biosynthesis may be regulated by an interaction between dietary n − 3 and n − 6 PUFA, as well as by levels of LC-PUFA, and this may, under certain nutritional conditions, lead to DHA production from C18 precursors. The molecular basis of putative fatty acyl ∆5 and ∆6 desaturation activities remains to be fully determined as thorough searches have found only a single (∆4) Fads2-type transcript. Therefore, further studies are required but this might represent a unique activity described within vertebrate fads.